Applying to College: The Role of Family Resources in Academic Undermatch. Issue 6 (June 2018) - Roksa, Josipa; Deutschlander, Denise
Background/Context: While K–12 research places parents at the center of understanding students' educational outcomes, empirical analyses of academic undermatch, and transition into higher education more broadly, have focused primarily on students' attitudes and behaviors. Family is implicitly present in the background but rarely brought to the fore. In this article, we integrate K—12 and higher education literatures to illuminate how family social and cultural capital are related to the probability of academic undermatch and to social class inequality in this outcome. Research Questions: We address three related questions: what is the relationship between family social and cultural capital and the probability of academic undermatch? To what extent is that relationship explained by students' college-going attitudes and behaviors? Finally, how do family social and cultural resources contribute to social class inequality in academic undermatch? Research Design: We use recent data from the Educational Longitudinal Study (ELS). ELS is a nationally representative sample of students who were 10th graders in 2002 and have been followed through the end of their high school education and into college. The analytical sample includes 5, 370 students. The outcome examined is academic undermatch in college application, which occurs when a student applies to colleges at a selectivity level below the selectivity of colleges the student is academically prepared to attend. Results: Family social and cultural capital play an important role in academic undermatch at the point of applying to college. More specifically, they influence students' attitudes regarding what is important to consider when choosing colleges (such as college costs and living at home) and students' college-going behaviors (primarily the variety of information sources consulted and the number of applications submitted). These variables collectively account for approximately 40% of the socioeconomic status (SES) gap in academic undermatch, net of controls. Moreover, we find no statistically significant interactions with SES, indicating that family resources, as well as specific attitudes and behaviors examined, benefit all students equally. Conclusion: Students' attitudes and behaviors related to college-going are deeply embedded in family contexts. Understanding academic undermatch, and college decisions more broadly, necessitates an explicit attention to family social and cultural resources, and mechanisms through which those resources are translated into specific educational outcomes. Policies and practices that aim to reduce social class inequality in college access would benefit from engaging parents, not only students.